Synthesis of Novel Pyridocarbazoles Analogues of Ellipticine - Meesala, Ramu; Ezzat, Mohammed Oday; Mordi, Mohd Nizam; Mansor, Sharif Mahsufi (Synlett, 2014)
Derivatives of pyrido[3,2-b]carbazole and pyrido[2,3-c]carbazole have been synthesized by the Vilsmeier–Haack reaction of N-(carbazol-3-yl)acetamides.
Keywords: pyrido[3,2-b]carbazoles; pyrido[2,3-c]carbazoles; N-(carbazol-3-yl)acetamides; Vilsmeier–Haack reagent